“Estrutura básica" e “Posição original” em The law of peoples de J. Rawls - Antônio Frederico Saturnino Braga (Ethic@: an International Journal for Moral Philosophy)
The aim of the present work is to compare the procedure followed in The Law of Peoples with the one followed in A Theory of Justice e Political Liberalism. I will try to show that, contrary to what Rawls claims, there are important differences between these two procedures, which originate in the conception of the basic structure, defined as the subject to which the principles of justice are applied. The differences in the concept of basic structure have important consequences on how the device of the original position is used at the international level. If Rawls had transferred to the international level the same conceptions of basic structure and original position used at the domestic case, the result would be a conception of international justice different from that which is adopted in The Law of Peoples.